A Variabel & Kriteria Pusat Inkubator Bisnis Universitas Palangka Raya: Variabel & Kriteria - Gantin, Adhitya; Adji, Fredyantoni F.; Wijanarka; Syahrozi; Ngini, Giris (JURNAL PERSPEKTIF ARSITEKTUR, 2025)
The University of Palangka Raya (UPR) plays a strategic role in fostering innovation and entrepreneurship based on the local potential of Central Kalimantan through the development of a business incubator center. However, the absence of purposedesigned and contextresponsive incubation facilities has become a major constraint in accelerating startup growth and the downstream commercialization of research outputs. This study aims to formulate a design concept for the University of Palangka Raya Business Incubator Center through a green architecture approach that is adaptive, sustainable, and responsive to user needs and the local environment. The research adopts a qualitative descriptive approach using a literature review and conceptual analysis to establish design variables and criteria for the business incubator. The design framework is developed through the integration of green architecture principles, tropical climatic characteristics, and the local potential of Central Kalimantan, including sustainable forestry, tropical agriculture and agroindustry, and culturebased creative economy sectors.The findings indicate that the application of conceptual variables and design criteriacomprising spatial functions and programs, hybrid incubator typology, spatial flexibility, indoor environmental comfort, tropical climate responsiveness, local cultural context, and environmental sustainabilitycan serve as a foundation for designing an adaptive and contextsensitive business incubator center. The integration of local potential into spatial strategies and architectural form strengthens the building’s identity while supporting sustainable development principles. Thus, the business incubator functions not only as an economic facility but also as a medium for learning, innovation, and the reinforcement of the university’s role in regional development.